Design and Synthesis of Novel Nordihydroguaiaretic Acid (NDGA) Analogues as Potential FGFR1 Kinase Inhibitors With Anti-Gastric Activity and Chemosensitizing Effect - Chen, Qian; Zhu, Min; Xie, Jingwen; Dong, Zhaojun; Khushafah, Fatehi; Yun, Di; Fu, Weitao; Wang, Ledan; Wei, Tao; Liu, Zhiguo; Qiu, Peihong; Wu, Jianzhang; et al. (Frontiers in Pharmacology, 2020)
Aberrant fibroblast growth factor receptor-1 (FGFR1), a key driver promoting gastric cancer (GC) progression and chemo-resistance, has been increasingly recognized as a potential therapeutic target in GC. Hereon, we designed and synthesized a series of asymmetric analogues using Af23 and NDGA as lead compounds by retaining the basic structural framework (bisaryl-1,4-dien-3-one) and the unilateral active functional groups (3,4-dihydroxyl). Thereinto, Y14 showed considerable inhibitory activity against FGFR1. Next, pharmacological experiments showed that Y14 could significantly inhibit the phosphorylation of FGFR1 and its downstream kinase AKT and ERK, thus inhibiting the growth, survival, and migration of gastric cancer cells. Furthermore, compared with 5-FU treatment alone, the combination of Y14 and 5-FU significantly reduced the phosphorylation level of FGFR1, and enhanced the anti-cancer effect by inhibiting the viability and colony formation in two gastric cancer cell lines. These results confirmed that Y14 exerted anti-gastric activity and chemosensitizing effect by inhibiting FGFR1 phosphorylation and its downstream signaling pathway in vitro. This work also provides evidence that Y14, an effective FGFR1 inhibitor, could be used alone or in combination with chemotherapy to treat gastric cancer in the future.